MORAL VALUES FOUND IN THE MOVIE ENTITLED “WONDER” BY R.J. PALACIO - Mutiara Aprillinda (Universitas PGRI Palembang, 2020)
Moral values as one of the important elements in the movie are also a very important role in our daily lives. In “Wonder” movie by R.J. Palacio, the author presents many moral values conveyed through the main character that is Auggie. The objective of this research was to investigate the moral values found in the “Wonder” movie by R. J. Palacio and the theoretical implication for teaching literature. A qualitative method was used to describe the dialogues/scenes that contain moral values with structural and psychological approaches. In this research, the writer used triangulation to ensure the validity of the data. The result of the research showed that there are ten moral values found in the “Wonder” movie, they are love and affection, struggle, kindness, bravery, self-confidence, forgiveness, honesty, wisdom, strong belief, courage. Hopefully, the students can learn and practice those positive moral values in their daily life. Therefore, by watching the movie, they not only get the entertainment but also moral messages which are implied in the story.